2018
DOI: 10.3390/su10082669
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Patent Blue (V) Dye Using Indian Bael Shell Biochar: Characterization, Application and Kinetic Studies

Abstract: The prospective utilization of bael shell (Aegle marmelos) as an agro-waste for the production of biochar was investigated along with its characterization and application for the abatement of hazardous aqueous Patent Blue (PB) dye solution. The sorptive removal of PB on bael shell biochar (BSB) was investigated under the following operational conditions: (pH, 2.7–10.4; biochar dosage, 2–12 g/L; and contact time, 0–60 min). The removal efficiency of PB by BSB in a batch adsorption experiment was 74% (pH 2.7 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…It is noteworthy to mention that the functional groups present in Sterculia alata biochar had a significant influence on the pHz values. The ∆pHz for Sterculia alata biochar was found to be 8.0, and this value is close to the value reported by Roy et al [17] for Bael shell biochar (8.8). In that study, the authors reported that the cationic contaminants can be adsorbed on Bael shell biochar when the pH value is greater than the pHz, while anionic compounds can be adsorbed at pH < pHz.…”
Section: Effect Of Point Of Zero Chargesupporting
confidence: 88%
See 2 more Smart Citations
“…It is noteworthy to mention that the functional groups present in Sterculia alata biochar had a significant influence on the pHz values. The ∆pHz for Sterculia alata biochar was found to be 8.0, and this value is close to the value reported by Roy et al [17] for Bael shell biochar (8.8). In that study, the authors reported that the cationic contaminants can be adsorbed on Bael shell biochar when the pH value is greater than the pHz, while anionic compounds can be adsorbed at pH < pHz.…”
Section: Effect Of Point Of Zero Chargesupporting
confidence: 88%
“…Similar results were obtained by [20,[30][31][32]. Roy et al [17] studied the adsorption of PB by the modified bael shell biochar (BSB) in the pH range of 2.7 to 10.4, and maximum sorption was perceived at pH 2.7. The percentage adsorption values of PB at seven of the tested initial pH values (i.e., 2.7, 4, 6, 7, 8, 9.2 and 10.4) were 74%, 62%, 58%, 55%, 47%, 40% and 39%, respectively.…”
Section: Effect Of Adsorbent Dosagesupporting
confidence: 75%
See 1 more Smart Citation
“…4 The fall in the adsorption capacities of the adsorbents for anionic dyes when raising the solution pH from acidic to alkaline was similar to that in the other studies. 2,3,17 Therefore, it can be concluded that a pH 3 was optimal for the adsorption of RR24 onto SBB-ZnO3 and CRHB-ZnO3, and the electrostatic attraction was the main mechanism for RR24 adsorption onto the biochars. Besides, there was also the contribution of pore lling, p-p interaction, and hydrogen bonding formation mechanisms in the adsorption process of RR24 onto the biochars.…”
Section: Effect Of Solution Phmentioning
confidence: 98%
“…15,16 Among adsorbents, biochars generated from agricultural wastes have widely been used to remove different pollutants. For example, bael shell (Aegle marmelos)-derived biochar was used for the treatment of patent blue dye 17 and corncob-derived biochar was employed for the removal of ammonia from simulated wastewater. 18 Out of agricultural wastes, cassava root husks (CRHs) and sugarcane bagasse (SB) have been widely used to produce biochars as low-cost non-toxic adsorbents for the removal of various pollutants from wastewater.…”
Section: Introductionmentioning
confidence: 99%